Dynamic control of aluminum morphology by wire and arc additive manufacturing based on image feedback - Wang, Xin; liu, Linlin; Zhou, Chen; Xu, Taojin; Luo, Maolin; Hu, Xiaolin (Frontiers in Materials, 2023)
The stability of the forming layer shape is a critical factor that impacts the final quality of sample morphology in wire and arc additive manufacturing (WAAM). This paper investigates the forming process and control methods to identify ways to optimize the process and improve the quality of the final product. The study aims to enhance the quality and precision of samples produced by the WAAM process by establishing a morphology control method based on image-feedback. The focus is on realtime image acquisition using CCD and simultaneous extraction of forming process morphology characteristics. Using central composite experimental design, a prediction model is developed to estimate key process parameters and feature sizes of deposits, including deposition height and width.To further analyze the dynamic characteristics of feature sizes of deposited layers, step response identification is conducted using three process parameters: forming speed, arc current, and wire feeding speed, as the system input. The experiments are designed to determine the weight of each process parameter and achieve a high level of response speed and precision. The findings indicate that the feature size of the deposited layer is most sensitive to changes in forming speed, followed by wire feeding speed, while arc current has the least impact on the feature size. After verification, the monitoring of the deposition height and width is found to be in good agreement with the prediction model, with an accuracy of over 90%. The results of this study can be used for size measurement and optimization of large aviation aluminum alloy components using WAAM technology, and to improve the quality of products produced using these processes.